Non-vitamin K Oral Anticoagulants and Anti-seizure Medications: A Retrospective Cohort Study - Ho, Chen-Jui; Chen, Shih-Hsuan; Lin, Chih-Hsiang; Lu, Yan-Ting; Hsu, Che-Wei; Tsai, Meng-Han (Frontiers in Neurology, 2021)
Abstract Purpose: Concerns of drug-drug interactions (DDIs) between anti-seizure medications (ASMs) and non-vitamin K oral anticoagulants (NOACs) have emerged in recent case reports and guidelines. Theoretically, the induction of hepatic cytochrome P 450 3A4 (CYP3A4) enzyme and permeability glycoprotein (P-GP) efflux transporter protein systems may reduce the effect of NOACs. We aimed to investigate whether such DDIs are clinically relevant in a real-world situation. Methods: We retrospectively reviewed 320 ischemic stroke patients with atrial fibrillation (Af) and grouped them according to different potential interactions with CYP3A4 and P-GP. Ischemic stroke events, transient ischemic attack (TIA) events, follow-up duration, baseline characteristics, concomitant ASMs, and stroke risk factors were collected. Statistical analysis included Kaplan-Meier survival curves and the log-rank test. Results: Overall, 320 ischemic stroke with Af patients received NOACs. Among the NOAC users, 75 also took ASMs, including 56 has potential DDIs: 43 (13.4%) were categorized as potential CYP and P-GP DDIs and 13 (4.1%) as P-GP only DDIs. The remaining 264 (82.5%) patients were used as controls including 19 exposed to non-significant DDI ASMs and 245 patients without ASMs exposure. The incidence rates of recurrent stroke/TIA events in both CYP3A4 and P-GP DDIs, P-GP DDIs only, and no DDIs were 7.5, 2.1, and 8.4/100 person-years, respectively. Kaplan-Meier survival curves and the log-rank test did not show significant differences among the groups. Conclusions: The recurrent stroke rate of NOAC users with potential DDIs was not higher than in those without potential DDIs in this single institute study. Our results suggest that theoretical interactions between ASMs and NOACs may not be as severe as previously thought in a real-world situation.